2019
DOI: 10.1111/ijac.13412
|View full text |Cite
|
Sign up to set email alerts
|

Nanowire‐decorated SiC foam from tissue paper and silicon powder by filter‐pressing

Abstract: A facile and scalable method for the preparation of low‐density SiC foam from tissue paper and silicon powder is reported. The co‐dispersion of pulp‐containing tissue paper micro‐ribbons and silicon powder is coagulated by adjusting the pH to 3.5. The silicon particles adhere to the tissue paper micro‐ribbons during the coagulation. The coagulated co‐dispersion on filter‐pressing consolidates the silicon particle‐decorated tissue paper micro‐ribbons and orients them perpendicular to the filter‐pressing directi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 51 publications
(72 reference statements)
0
2
0
Order By: Relevance
“…17 Wilson et al reported the formation of nanowire-decorated SiC foam from tissue paper and silicon powder by filter-processing technique. 18 Lee et al reported the carbothermal reduction process using a mixture of SiO 2 , carbon black, and phenolic resin to produce a porous SiC filter with SiC nanowires in the honeycomb structure. 19 Li et al reported SiC nanowire aerogel by polymer pyrolysis chemical vapor deposition (CVD) process in the pores of carbon foam.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Wilson et al reported the formation of nanowire-decorated SiC foam from tissue paper and silicon powder by filter-processing technique. 18 Lee et al reported the carbothermal reduction process using a mixture of SiO 2 , carbon black, and phenolic resin to produce a porous SiC filter with SiC nanowires in the honeycomb structure. 19 Li et al reported SiC nanowire aerogel by polymer pyrolysis chemical vapor deposition (CVD) process in the pores of carbon foam.…”
Section: Introductionmentioning
confidence: 99%
“…Wilson et al. reported the formation of nanowire‐decorated SiC foam from tissue paper and silicon powder by filter‐processing technique 18 . Lee et al.…”
Section: Introductionmentioning
confidence: 99%